Deteksi Bakteri Patogen Pada Daging Ayam Di Pasar Tradisional Hamparan Perak - Nuraini Sihotang; Kurniawan Sinaga; Alfath Rusdhi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Chicken meat is a source of animal protein for humans. The aim of this study was to detect pathogenic bacteria in chicken meat sold at the Silver Plain traditional market. The method used in this study is descriptive because research that describes the characteristics of a population or a phenomenon that is the object of research is trial and error. From the observational data analyzed descriptively as many as 10 samples from 10 traders obtained from the silver overlay market found the presence of Salmonella sp and Escherichia coli bacteria. The results showed that the highest number of colonies was found in trader 10, namely 3.8x106 cfu/g and the lowest in trader 5, namely 3.9x104 cfu/g, this was not in accordance with the maximum limit of microbial contamination in foodstuffs (fresh chicken meat) according to the National Standard. Indonesia (SNI) 7388:2009 namely TPC 1 x 106 colonies/gram. The results also showed that 70% of the chicken meat samples were contaminated with Salmonella sp bacteria, and 60% of the samples were contaminated with Escherichia coli bacteria. This shows that the quality of chicken meat sold in the Silver Plain traditional market does not meet the Indonesian National Standard (SNI) 7388:2009 Escherichia coli 1 x 101 colonies/gram, and Salmonella sp negative/25gram